Can Frequency Account for the Grammatical Choices of Children and Adults in Nominal Modification Contexts? Evidence from Elicited Production and Child-Directed Speech - Sanfelici, Emanuela; Schulz, Petra (Languages (Basel), 2021)
There is consensus that languages possess several grammatical variants satisfying the same conversational function. Nevertheless, it is a matter of debate which principles guide the adult speaker’s choice and the child’s acquisition order of these variants. Various proposals have suggested that frequency shapes adult language use and language acquisition. Taking the domain of nominal modification as its testing ground, this paper explores in two studies the role that frequency of structures plays for adults’ and children’s structural choices in German. In Study 1, 133 three- to six-year-old children and 21 adults were tested with an elicited production task prompting participants to identify an agent or a patient referent among a set of alternatives. Study 2 analyzed a corpus of child-directed speech to examine the frequency of passive relative clauses, which children, similar to adults, produced very often in Study 1. Importantly, passive relatives were found to be infrequent in the child input. These two results show that the high production rate of rare structures, such as passive relatives, is difficult to account for with frequency. We claim that the relation between frequency in natural speech and use of a given variant in a specific context is indirect: speakers may opt for the less grammatically complex computation rather than for the variant most frequently used in spontaneous speech.